Performance investigation of a passive battery thermal management system applied with phase change material. (March 2021) - Wang, Yanan; Wang, Zhengkun; Min, Haitao; Li, Hua; Li, Qingfeng
Highlights: A passive, low-cost battery thermal management system with PCM units was designed. It exhibited good heat storage capability and temperature equalization capability. After thermal insulation, a temperature retaining function could also be achieved. The effects of the parameters of the PCM unit on its thermal performance were got. The methods and results could provide reference for the design of BTMSs. Abstract: Lithium-ion batteries will produce a lot of heat during working, which can increase the temperature and temperature difference in the battery module, and seriously impair the capacity, life, and safety of the batteries. Therefore, an effective thermal management system should be implemented to control the temperature of the batteries, while reducing the energy consumption and cost of the system as much as possible. In this paper, a passive, low-cost battery thermal management system consisting of pouch lithium-ion cells and phase change material units is designed. Based on the heat production process of the battery and heat transfer theory of the phase change material, a numerical model is built and the performance of the thermal management system is analyzed. It is found that the phase change material units can effectively decrease the maximum temperature and the maximum temperature difference on the cell at the end of discharge, and thus have good heat storage capability and temperature equalization capability. After insulating heat dissipation from the surfaces of the phase change material units, a temperature retaining function can also be achieved. The effects of the design parameters of the phase change material unit on its thermal management performance are further investigated, including the thermal conductivity, viscosity, and latent heat of the phase change material, the thickness of the phase change material unit, and the thermal conductivity of the unit shell. It could provide theoretical references and technical means for the design and implementation of passive, low-cost battery thermal management systems applied with phase change materials.